Analysis of intellectual capital disclosure in cross-cultural E-tourism enterprises - Xuelian Liu (2018)
Purpose: The purpose of this paper is to present a framework for intellectual capital (IC) disclosure in cross-cultural E-tourism which includes identifying key success factors, as well as selecting indicators in operational level. Design/methodology/approach: The method described in this paper involves IC process model initiating from strategy formulation, following key success factors analyst by using a detailed interpretative structural model (ISM) instrument, and the indicators selection employing Delphi approach. The paper explicates methodological decisions associated with cross-cultural E-tourism context: selecting the appropriate specialists panel; the approach to data collection; and selecting the measurable indicators. Findings: This paper proposes three critical components of the framework: key success factors that based on an organization's strategies and contexts; indicators that measure and monitor the value of IC; an IC model that can help cross-cultural E-tourism enterprise improve management effectively. Originality/value: This paper extends the methodology developed previously to examine IC information in tourism enterprise. The paper introduces an alternative methodological paradigm to the study of IC measurement framework by employing the ISM. This exploratory study employs IC process model to build up cross-cultural E-tourism IC model, which is a start point for the value and performance research of this kind of enterprise. © Emerald Group Publishing Limited.